Advancing Road Safety in Urban Area: The Impact of Roundabouts on Intersection Design - Aziz, Fathan; Mahmudah, Noor; Augeri, Maria Grazia; Comi, Antonio (Journal of the Civil Engineering Forum, 2025)
Intersection represents a significant challenge around road traffic safety, posing a major problem, particularly during peak hour of urban road traffic. The high risk of accidents at this congested intersection is a serious concern, given that they involve a variety of road users, including vehicles and pedestrians. To address these challenges and minimize the risks related to intersections, roundabout have emerged as a significant effort. To address these challenges and minimize risks related to intersections, roundabouts have emerged as a notable solution. This approach does not only contribute to improved traffic flow but also enhances overall road safety by providing a more efficient alternative compared to conventional intersection designs. This study takes a comprehensive look at the safety performance of roundabouts as an alternative intersection design, by systematically reviewing relevant literature from Scopus and Google Scholar, aiming to explain how roundabout intersections contribute to crash reduction and traffic safety improvement. The analysis reveals that roundabouts generally lead to a significant reduction in severe collisions and enhance traffic flow efficiency. This is primarily due to their design, which minimizes conflict points and promotes lower vehicle speeds, and positively impacts the visibility and safety of pedestrian crossings. However, the roundabout has challenges, such as the requirement for drivers to adapt to new traffic patterns and the public's perception of the different aspects of the roundabout design. The findings indicate that roundabouts substantially improve road safety, evidenced by significant reductions in fatal and injury crashes. The literature also emphasizes the importance of customizing roundabout design and implementation to specific conditions, highlighting that such adapting is critical to maximizing benefits and ensuring positive impacts on road safety which is important to developed in further research.